A New Discourse on the Kitchen: Feminism and Environmental Education. (24th February 2015) - Stovall, Holly A.; Baker-Sperry, Lori; Dallinger, Judith M.; Leahy, Deana; Gray, Emily; Cutter-Mackenzie, Amy; Eames, Chris
<x content-type="archive" xml:space="preserve">Abstract</x> Popularised feminist discourse has devalued daily cooking and implicitly defined it as work that reinforces women's second-class status. In an era of climate change linked to industrialised foods and disease epidemics caused by the modern Western diet, kitchen work has acquired political importance. Daily cooking must be understood as public, as well as private. Neither feminist theorists nor environmental educators have integrated cooking in the kitchen, specifically, into discourse. By examining two local foods activist groups, we measure one site where feminists value cooking, and we develop a feminist theory of gender-inclusivity. Based on our survey, feminists who cook with local foods are only beginning to ideologically integrate feminism and sustainable foods cooking; however, we argue that in practice, the connection is strong and that it is time to conceptualise a new discourse on the kitchen for a feminist-environmental theory of cooking.